2019
DOI: 10.2147/ndt.s229284
|View full text |Cite
|
Sign up to set email alerts
|

<p>Thromboelastography with Platelet Mapping Detects Platelet Dysfunction in Patients with Aneurysmal Subarachnoid Hemorrhage with Rebleeding</p>

Abstract: BackgroundAneurysmal subarachnoid hemorrhage (aSAH) has high rates of disability and mortality, and aneurysm rebleeding is associated with poor functional outcomes. Thrombelastography with platelet mapping (TEG-PM) measures platelet function; however, it has not yet been researched in aSAH. We aimed to use TEG-PM to detect changes in platelet function in patients with aSAH and the difference in patients with and without rebleeding.MethodsWe retrospectively included patients with aSAH who underwent a TEG-PM tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…An important caveat to these preclinical studies is that they were performed in healthy volunteers and it is unclear the impact of common neurovascular disease states (e.g., ischemic stroke, subarachnoid hemorrhage) on platelet function. Data from patients with traumatic brain injury have demonstrated platelet dysfunction, and emerging data show a similar phenomenon in patients with aneurysmal subarachnoid hemorrhage 24,25 …”
Section: Discussionmentioning
confidence: 98%
“…An important caveat to these preclinical studies is that they were performed in healthy volunteers and it is unclear the impact of common neurovascular disease states (e.g., ischemic stroke, subarachnoid hemorrhage) on platelet function. Data from patients with traumatic brain injury have demonstrated platelet dysfunction, and emerging data show a similar phenomenon in patients with aneurysmal subarachnoid hemorrhage 24,25 …”
Section: Discussionmentioning
confidence: 98%
“…The authors confirmed that there was reduced ADP-and TRAP-mediated platelet aggregation, suggesting that the thrombin receptor pathway plays an important role in platelet dysfunction in head trauma. He et al analyzed platelet dysfunction in aSAH patients on admission to the hospital and found a significant decrease in platelet reactivity in response to AA and ADP [17]; moreover, high systolic blood pressure and inhibition of platelet activation after stimulation with AA and ADP were independent risk factors for re-bleeding in the multivariate logistic regression model. Quite the opposite results were documented in a later study by Frontera et al, who found that mean platelet activation was within the reference range regardless of the severity of early brain injury after aSAH, as classified on the Hunt-Hess scale [16].…”
Section: Discussionmentioning
confidence: 99%
“…Perez et al demonstrated increased activation and aggregation of platelets in SAH patients, especially after stimulation with ADP [15]. Different results were presented by Frontera et al, who showed that the mean activation of platelets remained within the reference range, regardless of the severity of SAH according to the Hunt-Hess scale [16] and by He et al, who demonstrated an inhibition of platelet activation in response to ADP and AA [17]. These ambiguous or even contradictory results indicate that in order to comprehensively determine hemostatic disorders in patients with intracranial bleeding, there should be a supplementary assessment of platelet function.…”
Section: Introductionmentioning
confidence: 97%
“…Adenosine diphosphate (ADP) agonists and arachidonic acid (AA) were added to measure the platelet inhibition of the P2Y12 receptor and cyclooxygenase pathways. Inhibition rate (%) is equal to (AA- or ADP-induced clot strength-fibrin clot strength)/(thrombin-induced clot strength-fibrin clot strength) × 100% ( 16 ). The percentage of platelet inhibition in response to ADP (ADPi) and MA-ADP (ADP-induced clot strength) were used to measure the response to clopidogrel.…”
Section: Methodsmentioning
confidence: 99%